An extraordinary new blind catfish, Xiurenbagrus dorsalis (Teleostei: Siluriformes: Amblycipitidae), from Guangxi, China - Xiu, Li-Hui; Yang, Jian; Zheng, Hui-Fang (Zootaxa, 2014)
Xiurenbagrus dorsalis, a new cave-dwelling amblycipitid catfish species, is described based on one specimen collected from the Pearl River drainage in Guangxi, China. The new species can be distinguished from congeners in having a unique combination of features, including the absence of eyes, long barbels, dorsal-fin origin posterior to vertical line at tip of pectoral fins and an adipose fin confluent with caudal fin. This is the first record of a blind catfish in China.